2014
DOI: 10.5194/nhessd-2-2597-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integration of HVSR measures and stratigraphic constraints for seismic microzonation studies: the case of Oliveri (ME)

Abstract: Because of its high seismic hazard the urban area of Oliveri has been subject of first level seismic microzonation. The town develops on a large coastal plain made of mixed fluvial/marine sediments, overlapping a complexly deformed substrate. In order to identify points on the area probably suffering relevant site effects and define a preliminary Vs subsurface model for the first level of microzonation, we performed 23 HVSR measurements. A clustering technique of continuous signals has been used to optimize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This study employed MAST System 354.20, which can provide simulation frequency of 0.8 -100 Hz, linear displacement up to 140 mm, angular displacement up to 9 deg., linear velocity up to 1700 mm/s, and linear acceleration up to 15.9 g. Detail specification of the MAST System 354.20 can be seen in Table 1 [23]. [3].…”
Section: Shaking Tablementioning
confidence: 99%
See 1 more Smart Citation
“…This study employed MAST System 354.20, which can provide simulation frequency of 0.8 -100 Hz, linear displacement up to 140 mm, angular displacement up to 9 deg., linear velocity up to 1700 mm/s, and linear acceleration up to 15.9 g. Detail specification of the MAST System 354.20 can be seen in Table 1 [23]. [3].…”
Section: Shaking Tablementioning
confidence: 99%
“…Ambient vibration measurement using a seismometer represent a non-invasive and non-destructive method for seismic-related studies, i.e., [1], [2], [3], and [4]. This method may inhibit widespread applications, i.e., assessing site fundamental frequency ( [5] - [8]), estimating bedrock level ( [9] - [14]), calculating building natural frequency [15], deducing shear wave velocity profile ( [16] - [20]).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the correlation between the H/V frequency peak and the fundamental resonance frequency of SH waves, being its use especially useful in urban environments (Bonnefoy-Claudet et al, 2008;Di Stefano et al, 2014;Endrun, 2011;Mundepi et al, 2010;Souriau et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have applied this method to assess the impact that seismic amplification has had on civil structures affected by past earthquakes [4,5], for the evaluation of the liquefaction potential of soils [6,7], for studies of amplification of areas for future civil projects [7,8], for the assessment of the impact of earthquakes on existing civil structures typical of urban environments [9][10][11], in studies related to landslides [12,13], in coastal and port areas [4,9,14,15] and for the site characterization of seismic stations [16][17][18]. In Panama, several studies have been carried out on the estimation of side effects in some cities [19][20][21].…”
Section: Introductionmentioning
confidence: 99%